"And when will you install the new water pump?": disconcerted reflections on how to be a 'good' Global Health scholar - Robert A.J. Borst; Rik Wehrens; Roland Bal (BMC, 2023)
Abstract Background While critique on Global Health is not new, recent years show a surge of criticism on the field's colonial legacy and practices specifically. Such accounts argue that despite Global Health's strive for universality and equity in health, its activities regularly produce the opposite. The epistemic privileging of Northern academics and scientific method, further augmented by how Global Health funding is arranged, paints a picture of a fragmented field in which 'doing good' has become a normatively laden and controversial term. It is specifically this controversy that we seek to unpack in this paper: what does it take to be a 'good' Global Health scholar? Results We used Helen Verran's notion of 'disconcertment' to analyse three auto-ethnographic vignettes of Robert's Global Health 'fieldwork'. We illustrate that disconcertment, a bodily and personalised experience of unease and conflicting feelings, may serve as an important diagnostic of conflicting imperatives in Global Health. Robert's fieldwork was entangled with incongruous imperatives which he constantly had to navigate through and that repeatedly produced disconcertment. The contribution that we seek to make here is that such disconcertment is not something to defuse or ignore, but to take seriously and stay with instead. Conclusion Staying with the disconcertment serves as a starting point for conversations about 'doing good' in Global Health fieldwork and creates opportunity for making Global Health teaching and projects more reflexive. The paper thereby positions itself in discussions about fair collaborations between the Global North and South and our analysis offers a set of considerations that can be used by Northern scholars to critically reflect on their own role within Global Health.